Management of post-partum haemorhage at tertiary care center - Patel, Tejal L.; Shah, Prachi G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: In developing countries like India post-partum haemorrhage (PPH) contributes to 35% of all maternal deaths and 239 per 1,00,000 deaths. So, PPH is a high-risk condition which increases maternal morbidities and mortalities. Hence it mandates a multidisciplinary approach. Audit of misses and near misses helps to determine causes of maternal morbidity and mortality and identify gaps in care. Aim of the study was to study conservative and definitive management of PPH. Methods: A retrospective analysis of all patients who has undergone PPH and also cases who referred from outside with PPH in department of obstetrics and gynaecology at civil hospital Ahmedabad from January 2021 to January 2022. Results: Out of 6029 deliveries there were 171 cases of PPH (2.8%). Which of 150 cases (87.7%) managed by conservative management (uterine conserving) and 21 (12.3%) cases were required definitive management (hysterectomy) due to failure of conservative management. Out of all cases 78.8% cases of PPH were due to atonicity of uterus and 19.1% cases were due to traumatic cause. Early recourse to hysterectomy was recommended especially where bleeding is associated with morbidly adherent placenta. Conclusions: PPH is an important cause of morbidity and mortality. We now have more options for conservative management which can greatly reduce its sequelae and more importantly in patients with wider issues of reproductive health. But in case of intractable bleeding and non-responsive by conservative management definitive management (Hysterectomy) is life saving and last resource.